Protective effect of liraglutide on experimental testicular ischaemia reperfusion in rats. (6th February 2021) - Degirmentepe, Recep B.; Altunrende, Fatih; Bozkurt, Muammer; Merder, Erkan; Otunctemur, Alper; Sonmez, Kivilcim; Yildirim, Funda; Ada, Saniye; Isman, Ferruh K.; Cekmen, Mustafa B.
Abstract: This study was performed to evaluate the effect of liraglutide on experimental testicular ischaemia reperfusion in rats in terms of biochemistry, histopathology and immunohistochemistry. A total of 28 male Wistar‐Albino rats were divided randomly into 4 groups: control (7), sham (7), ischaemia‐reperfusion (7) and ischaemia‐reperfusion + liraglutide (7). Biochemically, Nitric Oxide, Malondialdehyde, Superoxide dismutase, Glutathione peroxidase and Catalase levels were measured in the testis. Apoptosis protease activating factor‐1 and inducible nitric oxide synthase activity were evaluated immunohistochemically as well. Statistical analyses were made via the Kruskal–Wallis and Mann–Whitney U tests. In the reperfusion group, CAT and SOD values were increased ( p > .05), NO and MDA values were decreased ( p < .05) after administration of liraglutide. In addition, GPx values were significantly increased in ischaemia reperfusion + liraglutide administered group compared to reperfusion group ( p < .05). Apaf‐1 and iNOS activity were significantly decreased with the addition of liraglutide treatment to the ischaemia‐reperfusion group ( p < .05). First of all, we would like to say that liraglutide treatment is moderately preventive against I/R injury in testicular torsion. The anti‐inflammatory, antioxidant and antiapoptotic properties of liraglutide are create a moderately protective effect as we show in this study.